A 3-Dimensional In Vitro Model of Zonally Organized Extracellular Matrix. (December 2021) - Walzer, Sonja M.; Toegel, Stefan; Chiari, Catharina; Farr, Sebastian; Rinner, Beate; Weinberg, Annelie-Martina; Weinmann, Daniela; Fischer, Michael B.; Windhager, Reinhard
Objective: Functional cartilage repair requires the new formation of organized hyaline cartilaginous matrix to avoid the generation of fibrous repair tissue. The potential of mesenchymal progenitors was used to assemble a 3-dimensional structure in vitro, reflecting the zonation of collagen matrix in hyaline articular cartilage. Design: The 3-dimensional architecture of collagen alignment in pellet cultures of chondroprogenitors (CPs) was assessed with Picrosirius red staining analyzed under polarized light. In parallel assays, the trilineage capability was confirmed by calcium deposition during osteogenesis by alizarin S staining and alkaline phosphatase staining. Using reverse transcription–quantitative polymerase chain reaction (RT-qPCR), mRNA levels of ALP, RUNX2, and BGLAP were assessed after 21 days of osteoinduction. Lipid droplets were stained with oil red O and adipogenic differentiation was confirmed by RT-qPCR analysis of PPARG and LPL gene expression. Results: Under conditions promoting the chondrogenic signature in self-assembling constructs, CPs formed an aligned extracellular matrix, positive for glycosaminoglycans and collagen type II, showing developing zonation of birefringent collagen fibers along the cross section of pellets, which reflect the distribution of collagen fibers in hyaline cartilage. Induced osteogenic and adipogenic differentiation confirmed the trilineage potential of CPs. Conclusion: This model promotes the differentiation and self-organization of postnatal chondroprogenitors, resulting in the formation of zonally organized engineered hyaline cartilage comparable to the 3 zones of native cartilage.